A narrative review of the interconnection between pilot acute stress, startle, and surprise effects in the aviation context: Contribution of physiological measurements - Diarra, Moussa; Marchitto, Mauro; Bressolle, Marie-Christine; Baccino, Thierry; Drai-Zerbib, Véronique (Frontiers in Neuroergonomics, 2023)
Aviation remains one of the safest modes of transportation. However, an inappropriate response to an unexpected event can lead to flight incidents and accidents. Among several contributory factors, startle and surprise, which can lead to or exacerbate the pilot's state of stress, are often cited. Unlike stress, which has been the subject of much study in the context of driving and piloting, studies on startle and surprise are less numerous and these concepts are sometimes used interchangeably. Thus, the definitions of stress, startle, and surprise are reviewed, and related differences are put in evidence. Moreover, in the context of recent advances of assessment methods for stress, startle effect and surprise, we investigate how physiological measures could be later used in ecological cockpit design evaluations. Finally, we draw some perspectives to set up further studies focusing specifically on these concepts and their measurement.